Енергозберігаюче керування асинхронними електродвигунами прикладеною напругою - Вовк, Олександр Юрійович; Вовк, Александр Юрьевич; Vovk, Oleksandr; Квітка, Сергій Олексійович; Квитка, Сергей Алексеевич; Kvitka, Serhii (ТДАТУ, 2020)
UK: У статті розглянуто один із шляхів вирішення народно-господарської проблеми заощадження електроенергії при роботі асинхронних електродвигунів, що застосовуються для приводу робочих машин потокових технологічних ліній. Показано, що всі існуючі системи енергоефективного керування асинхронними електроприводами не враховують види механічних характеристик робочих машин. Проаналізовано з точки зору енергозбереження процес електромеханічного перетворення енергії асинхронних електродвигунів. Отримано залежності живлячої напруги від завантаження асинхронних електродвигунів приводу робочих машин з різними видами механічних характеристик, які дозволяють здійснювати управління асинхронними електроприводами за допомогою прикладеної напруги з урахуванням мінімуму втрат активної потужності в електродвигуні. Наведено результати аналітичних досліджень. RU: В статье рассмотрен один из путей решения народно-хозяйственной проблемы энергосбережения при работе асинхронных электродвигателей, применяемых для привода рабочих машин поточных технологических линий. Показано, что все существующие системы энергоэффективного управления асинхронными электроприводами не учитывают виды механических характеристик рабочих машин. Проанализированы с точки зрения энергосбережения процесс электромеханического преобразования энергии асинхронных электродвигателей. Получены зависимости питающего напряжения от загрузки асинхронных электродвигателей привода рабочих машин с различными видами механических характеристик, которые позволяют осуществлять управление асинхронными электроприводами с помощью приложенного напряжения с учетом минимума потерь активной мощности в электродвигателе. Приведены результаты аналитических исследований. EN: The article discusses one of the ways to solve the national economic problem of energy saving during the operation of three-phase asynchronous electric motors used to drive working machines of production lines. The existing systems of energy efficient control of asynchronous electric drives are considered and it is shown that all of them do not take into account the types of mechanical characteristics of working machines. This fact is reflected in the accuracy of electric motor control to minimize electricity consumption. Using the L-shaped equivalent circuit, the process of electromechanical energy conversion in asynchronous electric motors used to drive working machines with various types of mechanical characteristics that operate under load conditions is analyzed from the point of view of energy saving. As a result of the analysis, equations were obtained for the total losses of active power in an asynchronous electric motor, depending on the coefficient of deviation of the applied voltage, load factor, design parameters of the electric motor and the type of mechanical characteristics of the working machine. The dependences of the voltage deviation coefficient on the load coefficient of asynchronous electric motors of the drive of working machines with various types of mechanical characteristics are obtained. By approximating these dependencies, equations are obtained that make it possible to control asynchronous electric drives using the applied voltage, taking into account the minimum active power losses in the electric motor. A technique has been developed for energy-saving control of asynchronous electric motors using an applied voltage. The results of analytical studies are presented. The obtained equations can be used in the design of energy-saving control devices.
Энергосберегающее управление асинхронными электродвигателями приложенным напряжением
Energy saving control of asynchronous electric motors with applied voltage
Keywords: асинхронний електродвигун; втрати потужності; робоча машина; навантаження; енергозбереження; керування; механічна характеристика; асинхронный электродвигатель; потери мощности; рабочая машина; нагрузка; энергосбережение; управление; asynchronous motor; power loss; equivalent circuit; work machine; energy saving; control; mechanical characteristic; slip